2018
DOI: 10.1371/journal.ppat.1006839
|View full text |Cite
|
Sign up to set email alerts
|

Viral manipulation of STAT3: Evade, exploit, and injure

Abstract: Signal transducer and activator of transcription 3 (STAT3) is a key regulator of numerous physiological functions, including the immune response. As pathogens elicit an acute phase response with concerted activation of STAT3, they are confronted with two evolutionary options: either curtail it or employ it. This has important consequences for the host, since abnormal STAT3 function is associated with cancer development and other diseases. This review provides a comprehensive outline of how human viruses cope w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 133 publications
2
74
0
1
Order By: Relevance
“…When observing a fierce induction of gene expression downstream the IL6-JAK-STAT3 signaling cascade in PCV2 patients (Fig S2A), STAT3 emerges as a druggable candidate host factor. Interestingly, STAT3 is a key regulator of inflammation often exploited by viruses with pathogenic consequences [28]. In a drug assay, treatment with selective STAT3 inhibitor Cpd188 exhibits a dose-dependent effect on PCV2 infection in PPLs at 72 hpi (Fig 6A).…”
Section: Resultsmentioning
confidence: 99%
“…When observing a fierce induction of gene expression downstream the IL6-JAK-STAT3 signaling cascade in PCV2 patients (Fig S2A), STAT3 emerges as a druggable candidate host factor. Interestingly, STAT3 is a key regulator of inflammation often exploited by viruses with pathogenic consequences [28]. In a drug assay, treatment with selective STAT3 inhibitor Cpd188 exhibits a dose-dependent effect on PCV2 infection in PPLs at 72 hpi (Fig 6A).…”
Section: Resultsmentioning
confidence: 99%
“…Further, the suppression of SOCS7 has been reported to activate STAT3 protein which promotes inflammation . The STAT3 has been reported to either activate the immune responses through IL‐6 or suppress the inflammatory responses by activating the antiinflammatory cytokine IL‐10 signaling . The modulation of STAT3 has been reported among various viruses which promote viral replication and persistence .…”
Section: Discussionmentioning
confidence: 99%
“…44 The STAT3 has been reported to either activate the immune responses through IL-6 or suppress the inflammatory responses by activating the antiinflammatory cytokine IL-10 signaling. 45 The modulation of STAT3 has been reported among various viruses which promote viral replication and persistence. 46,47 There are reports on CHIKV-induced inflammation and prolonged virus persistence, therefore, the suppression of SOCS7 by hsa-miR-4299 and activation of STAT3 may have a role in CHIKV persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Several oncogenic viruses activate STAT3 to drive cellular proliferation, viral replication and tumourigenesis [18]. Using a primary cell culture model, we have previously shown that E6 activates the STAT3 signalling pathway in primary keratinocytes during the HPV lifecycle [19].…”
Section: Discussionmentioning
confidence: 99%